2006
DOI: 10.1159/000089298
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Vaginosis and Group B Streptococcal Colonization and Preterm Delivery in a Low-Risk Population

Abstract: Objective: To evaluate the relationship between bacterial vaginosis (BV) and group B streptococcal (GBS) colonization in the 2nd trimester of pregnancy and preterm delivery. Methods: 1,197 pregnant women between 22 and 25 weeks’ gestation had a high vaginal swab for assessment of BV and GBS. Exclusion criteria were: previous preterm delivery, or mid-trimester abortion or termination of pregnancy, multiple gestation, oligo- or polyhydramnios, placenta previa, fetal abnormalities, uterine malformations, cervical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 48 publications
0
7
0
1
Order By: Relevance
“…The observed PTB rate of 7% in this study is similar to the expected rate in Flanders during the same period (7.4%; singletons 6.3%) 11 . Numerous studies have consistently shown that bacterial vaginosis and AVF at 12–24 weeks are associated with increased risks of PTB, preterm rupture of the membranes, chorioamnionitis, fetal infection and cerebral palsy 12–22 . However, studies applying strict criteria for full bacterial vaginosis (a Nugent score above 7, overall granular flora, >20% clue cells and LBG III) did not find a significant correlation between BV and the risk of PTB 14,18,23 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The observed PTB rate of 7% in this study is similar to the expected rate in Flanders during the same period (7.4%; singletons 6.3%) 11 . Numerous studies have consistently shown that bacterial vaginosis and AVF at 12–24 weeks are associated with increased risks of PTB, preterm rupture of the membranes, chorioamnionitis, fetal infection and cerebral palsy 12–22 . However, studies applying strict criteria for full bacterial vaginosis (a Nugent score above 7, overall granular flora, >20% clue cells and LBG III) did not find a significant correlation between BV and the risk of PTB 14,18,23 …”
Section: Discussionmentioning
confidence: 99%
“…11 Numerous studies have consistently shown that bacterial vaginosis and AVF at 12-24 weeks are associated with increased risks of PTB, preterm rupture of the membranes, chorioamnionitis, fetal infection and cerebral palsy. [12][13][14][15][16][17][18][19][20][21][22] However, studies applying strict criteria for full bacterial vaginosis (a Nugent score above 7, overall granular flora, >20% clue cells and LBG III) did not find a significant correlation between BV and the risk of PTB. 14,18,23 Helen McDonald pointed out in the early 1990s that women with an increased risk for PTB have two types of AVF, one consisting of predominantly BV flora, and the other of aerobic microorganisms, such as Klebsiella and Escherichia coli.…”
Section: Discussionmentioning
confidence: 99%
“…Microorganisms that cause BV can ascendantly spread from lower parts of genital tract to upper parts and lead to chorioamnionitis, a preterm rupture of fetal membranes and preterm delivery 3,25,26 . Then, microorganisms can produce proteolytic enzymes that increase epithelium permeability in vagina, and allow passage of very pathogenic microorganisms 27,28 . Results of other researches indicate the role of local immunological factors, genetically predisposed and depending on their presentation to microorganisms causing BV, local inflammatory mediators such as cytokines, chemokines, and growth factors that determine what kind of consequences will appear.…”
Section: Discussionmentioning
confidence: 99%
“…failed to reduce the risk of preterm birth (P ¼ 0.84). Studies of bacterial vaginosis in pregnancy and preterm birth published since 2003 continue to emphasize an inconsistency of existing evidence(Table 3)[16,23,[61][62][63][64][65][66][67][68][69][70][71][72][73][74][75][76][77][78]. Two additional RCTs have been consequently published but failed to replicate the findings of the Cochrane review, though this may represent the use of different treatment approaches[61,62].…”
mentioning
confidence: 99%